Literature Review: Penerapan e-Filing dalam Pelaporan SPT Tahunan Formulir 1770SS bagi Wajib Pajak Orang Pribadi - Mochamad Abdurrochman Faiz; Condro Widodo (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This literature review explores the implementation of the e-Filing system in submitting the Annual Tax Return for individual taxpayers (Form 1770SS) and its contribution to improving administrative efficiency and tax compliance. As a digital innovation, e-Filing simplifies the tax reporting process by allowing taxpayers to file their returns independently, quickly, and transparently without time or location constraints. However, the system’s overall effectiveness depends on the level of digital literacy, understanding of tax regulations, and quality of service provided by tax authorities. The main challenge arises from taxpayers with limited technological proficiency and inadequate tax knowledge, who still require continuous assistance and guidance. Therefore, successful implementation of e-Filing requires not only technological innovation but also targeted tax education programs and a more personalized service approach. By integrating these elements, e-Filing can enhance taxpayer trust, facilitate compliance, and strengthen the effectiveness of digital tax administration in achieving sustainable tax governance.